Beyond binary oppositions: a meta-synthesis of China’s cultural translation strategies for global communication - Sanjun Sun; Lijie Zhao; Xiaoyan Zhou (Humanities & Social Sciences Communications)
Abstract This study synthesizes scholarly perspectives on China’s cultural translation strategies through qualitative meta-synthesis of 650 research articles from leading Chinese academic journals (2001–2020). Using Lasswell’s communication model, the study analyses five dimensions: stakeholders, content selection, dissemination channels, audiences, and impact assessment. Findings reveal that successful cultural translation balances competing priorities rather than following binary oppositions. Research attention is distributed unevenly across dimensions—stakeholder dynamics and content selection receive substantial focus while impact assessment remains significantly underexplored. Analysis shows scholarly preference for collaborative translation approaches combining Chinese cultural knowledge with target language fluency. Content selection analysis identifies tension between traditional and contemporary works, with classical literature dominating academic discourse despite evidence suggesting modern works better engage international audiences. The paper proposes three frameworks emerging from the synthesis: the Integrated Expert Network Model formalizing multi-stakeholder collaboration; the Audience Integration Framework incorporating systematic feedback mechanisms; and the Tiered Support Model balancing cultural significance with market potential. This research contributes to translation studies by systematically mapping scholarly discourse, identifying effective practices, and proposing structured approaches that can inform translation policy beyond the Chinese context.